2019
DOI: 10.1001/jamadermatol.2019.1121
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of Serious Infection in Patients Receiving Systemic Medications for the Treatment of Psoriasis

Abstract: IMPORTANCE There is a need for better understanding of the comparative safety of systemic medications used in the treatment of psoriasis. OBJECTIVE To compare the risk of serious infection associated with biologic and nonbiologic systemic medications in patients with psoriasis. DESIGN, SETTING, AND PARTICIPANTS An observational cohort study was conducted using medical and outpatient pharmacy claims from 2 large US health insurance claims databases from January 1, 2003, through September 30, 2015. We included p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 41 publications
2
83
0
1
Order By: Relevance
“…There is no signal of excess infections related to the use of ustekinumab trials in IBD, and no excess risk of infection was reported in psoriasis. 19 Exposure to Janus kinase (JAK) inhibitors is associated with an increased risk of various infections, mainly herpes zoster. Based on data from randomized clinical trials of tofacitinib in ulcerative colitis, 20 the absolute risk of herpes zoster in patients aged older than 65 years is 95.5 events per 1000 person-years.…”
Section: Risks Levels and Patients At Riskmentioning
confidence: 99%
“…There is no signal of excess infections related to the use of ustekinumab trials in IBD, and no excess risk of infection was reported in psoriasis. 19 Exposure to Janus kinase (JAK) inhibitors is associated with an increased risk of various infections, mainly herpes zoster. Based on data from randomized clinical trials of tofacitinib in ulcerative colitis, 20 the absolute risk of herpes zoster in patients aged older than 65 years is 95.5 events per 1000 person-years.…”
Section: Risks Levels and Patients At Riskmentioning
confidence: 99%
“…It does not suppress the immune system to the extent of the other conventional treatments for psoriasis. In an observational cohort study, there was no increased rate of overall serious infections among acitretin‐treated psoriasis patients vs methotrexate; acitretin increased risk of cellulitis compared to methotrexate (propensity score‐adjusted hazard ratio [HR], 1.76; 95% confidence interval [CI], 1.11‐2.80), possibly due to skin fragility and Staphylococcus aureus colonization 15 . Therefore, acitretin has not shown increased viral/respiratory infection risk and can be safely used during the pandemic.…”
Section: Nonbiologic Systemic Therapiesmentioning
confidence: 99%
“…No cases of tuberculosis reactivation were reported 54 . In one observational cohort study of 107 707 systemically treated psoriasis patients, ustekinumab (HR: 0.65; 95% CI, 0.47‐0.89), apremilast (HR: 0.50; 95% CI, 0.26‐0.94) and etanercept (HR: 0.75; 95% CI, 0.61‐0.93) had decreased risks of overall serious infections compared with methotrexate 15 . Similar risks of infection between ustekinumab and placebo were reported by Lebwohl et al 59 Thus, treatment with ustekinumab may be considered relatively safe during the COVID‐19 pandemic; however, switching to specific IL‐23 inhibitors may be prudent.…”
Section: Nonbiologic Systemic Therapiesmentioning
confidence: 99%
“…It is important to understand whether these findings from RCTs persist in real-world practice, where patients are more heterogeneous and drug utilisation is far less controlled 7. Evidence from observational studies between biologic and non-biologic drugs have yielded inconsistent findings: some have shown an increased risk,8 9 while others have not found a difference 10–14. To our knowledge, no published studies have yet quantified the comparative real-world risk of serious infections among IL-17, IL-12/23 and TNF inhibitors.…”
Section: Introductionmentioning
confidence: 99%